O romance policial: a construção do suspense em Suicidas, de Raphael Montes - Duvanel, Fernanda Ferreira (2024)
This study aims to investigate the construction of suspense in Suicidas, by Raphael Montes, in the context of the contemporary Brazilian crime novel, seeking to understand how suspense is created through the narrative procedures and strategies employed by the author, as well as analyzing the relationship between reality and fiction and the impact of this relationship on the representation of extreme violence in the plot. The analysis points out that Montes builds psychological suspense through temporal alternations and variations in narrative focus, using audiovisual language techniques. His strategies are permeated by a type of realism which, under the narration of a writer character who assumes the position of double – fictional-writer and empirical writer - dissolves the thresholds between reality and fiction. In addition, the author incorporates an aesthetic violence that seeks to cause intense sensations, accentuating the effect of suspense. The analysis is based on a bibliographical review of the detect